Students' information-seeking intention in academic digital libraries - Faeizah Salim; Bavani Saigar; Pravin Kumar Armoham; Sarasvathy Gobalakrishnan; Yen, Michelle Pin Jap; Nurul Akidah Azmaya Lim (IGI Global, 2016)
The purpose of this research is to examine students' information-seeking intention regarding academic digital library services guiding by the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB). Data was collected among students in a public higher learning institution in Federal Territory of Labuan Malaysia. The empirical result of the hierarchical regression had confirmed that students' intention to seek for information in digital library was influenced mainly by their attitude, implying that, in predicting the information-seeking intention in an academic digital library with TPB was much better than TRA. The findings of the research provide broader insights for the academic digital libraries to be more aware of the important factors that influence library users in seeking for information and fulfil their requirement. A new motion can be developed by using the result of this research, which improve the knowledge from previous studies via the assessment from TPB.